Risk factors for Anal Sphincter Tears - Rashda Imran, Humera Nasir, Iram Naz (Journal of Rawalpindi Medical College, 2012)
Background: To determine risk factors in cases of third and fourth degree anal sphincter damage during vaginal deliveries. Methods: In this descriptive study all women with recognized third or fourth degree perineal tear were included .The main outcome measures were relationship with parity, weight of baby and mode of delivery.In all patients end to end anastomosis technique was used to repair the tear. Results: A total no of 57(1.8%) were identified to have sustained anal sphincter complex damage out of 3076 vaginal deliveries. The mean age was 25.65 +_4.6 years. Majority 52 (91.2%) were between 20-35 years and 3 (5.26%) > 35years.Most commonly the tears were seen in patients of reproductive age group. The primipara or primigravidas had highest frequency of anal sphincter damage(71.9%).Thirty three (57.9%) had spontaneous vaginal deliveries (SVD) , 11 (19.3%) SVD with episiotomy, 11 (19.3%) forceps and 1 (1.75%) vacuum delivery. Majority (63.16%) delivered babies between 2500- 3500 grams. Conclusion: Anal sphincter damage is strongly associated with first vaginal delivery. Forceps delivery as compared to vacuum delivery has higher rate of third and fourth degree tears. Mediolateral episiotomy may have protective role.